“BYSTANDER EFFECT” IN CASES OF CORRUPTION IN CORPORATE, BUREAUCRATIC AND POLITICAL ORDERS - Vera Astuti; Ratna Candra Sari (Jurnal Hukum dan Peradilan, 2019)
E-KTP Corruption is an organized crime that occurs in Indonesia. The corruption that has been established is to form an organized network due to the phenomenon "baystander effect" where it is a phenomenon of social psychology due to the loss of a sense of virginity to act to do something on an incident that Characterized by the interdependent nature of each other which eventually nothing moves one.  This research aims to prove the existence of a matter of silence because it is triggered by personal interests or "self-interest" of the persons involved until difficult to control by the State apparatus. This method of research refers to the reference of legislation, information submitted by the media, statements from politicians and bureaucracy officials, court decisions and also reference books. The results of the study showed that the corruption that ensnares the bureaucracy officials and the politicians in fact has also dragged corporations. Participating in the case of the persons in corruption cases of intertwining creates a crime that is organized in such a way to harm the country and cause millions of people to be injured in the sleep. When they feel benefited over this corruption case then they choose silence, this is the phenomenon called "baystander effect" thus complicating the investigation in dismantling this corruption case.